Geometric phase for investigation of nanostructures in approaches of polarization-sensitive optical coherence tomography - Zenkova, C.Yu.; Angelsky, O.V.; Ivanskyi, D.I.; Chumak, M.M. (Physics and Chemistry of Solid State, 2023)
Proposed paper presents the latest results in the framework of polarization-sensitive low-coherence interferometry related to new approaches for using the geometric phase to reproduce the polarization structure of a biological transparent anisotropic micro (nano) object. The polarization parameters of an anisotropic object are measured in real time on the basis of a modified Mach-Zehnder interferometer. The advantage of using the geometric phase is the diagnostic of polarization anisotropic surface (subsurface) nanosized layers in a non-contact, non-invasive manner.